ANALISIS MODULUS ELASTISITAS LENTUR TERHADAP LOSS FACTOR BETON POLIMER - Mohd. Isneini (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2009)
Polimer concrete has different behaviour and different mechanic characteristic than othersbecause it depends on material polimer that are used, so that it caused to be researched and bestudied its behaviour and dynamic characteristic. This polimer concrete was made of prepackedsystem, consisted of unsaturated polyester (UP) added with styrene monomer (SM) as bindermatrix, cobalt napthenate solution (CoNp) as a promotor and methyl ethyl ketone peroxide(MEKPO) as an initiator, and coarse aggregate as inclusion. In this composition, variation ofpolymer concrete based on percentage of polimer and fly ash as a filler, and any other materialswere keeped in constant. The object of this research, to find out values of damping (loss factor),dynamic parameter,and then compare it with flexural modulus elasticity, so that series oflaboratory tests were carried out. Test results showed, values of damping (loss factor) 1,669 –3,017%. Results also showed that much and much more content of polymer caused loss factor(????), damping coeffisien (c) and damping ratio (????) decrease, however it showed that fly ashaffected to increase value of dynamic parameter. When analising damping factor of polimerconcrete, it’s suggested to use flexural modulus elasticity because both of flexural modulus andloss factor (modal test) showed the same flexural behaviour.